Identification of Premature Deindustrialization and Its Acceleration in Indonesia (Period 1986-2015) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2018)
The increase of the manufacturing's share in GDP has reached its peak in the early 2000s while the growth rate of the manufacturing employment is relatively low. Both facts demonstrate that the process of industrialization has slowed down and an indication of deindustrialization in Indonesia. Deindustrialization that occurs in the countries with low GDP per capita is called premature deindustrialization. This study measures the rate of deindustrialization and identification of premature deindustrialization on period 1986- 2015. The result shows that the speed of deindustrialization varies between indicators and between islands. Descriptive analysis showed indication of premature deindustrialization in Indonesia. Keywords: Deindustrialization, Premature deindustrialization, Manufacturing, Indonesia JEL classification: L16, L50, L52, L60, O14, O25